Violence and society (1993)
Conflict is the basis of all social ties. The aggressive drives, proper to humanity according to Freud, tend to dissolve these bonds. Therefore, no society can escape from violence. The function of culture is to promote transformations in its manifestations, making possible social agreement, which does not mean elimination of all conflict.